The Immunomodulatory Activities of Saurauia vulcani Korth Leaves towards RAW 264.7 cell - Rosidah, R; Yuandani, Y; Widjaja, Sri Suryani; Lubis, Muhammad Fauzan; Satria, Denny (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Saurauia vulcani Korth is an actinidiaceae family plant that is used as traditional medicine by the community. Testing the immunomodulatory effect of Saurauia vulcani Korth extract was done in vitro on RAW cells line by stratified extraction using n-hexane, ethyl asetat, and ethanol solvents. Determination of nitric oxide levels by the griess method and inhibition of gene expression TNF-α, IL6, COX-2, IL-1β, and iNOS by RT-PCR method. Saurauia vulcani Korth extract (NESVL, EAESVL, and EESVL) at a concentration of 25 ug / ml was able to reduce the value of nitric oxide in RAW cells 246.7 and was able to inhibit the expression of genes TNF-α, IL-6, COX-2, IL-1β, and iNOS. Where the density value of each band formed by 1.21 ± 0.005; 1.15 ± 0.005; 0.88 ± 0.003 on TNF-α, 1.23 ± 0.003; 1.64 ± 0.005; 0.55 ± 0.003 on IL-6, 0.38 ± 0.003; 0.55 ± 0.003; 0.38 ± 0.003 on COX-2, 0.18 ± 0.003; 0.04 ± 0.003; 0.03 ± 0.003 on IL-1β, and 0.30 ± 0.003; 0.41 ± 0.003; 0.11 ± 0.005 on iNOS.